Talent acquisition and technology: A step towards sustainable development - Rehman, Saqib; Ullah, Aman; Naseem, Khalida; Elahi, Ali Raza; Erum, Humaira (Frontiers in Psychology, 2022)
Purpose: The purpose of the research is to highlight the use of social media and information technology in employee recruitment by providing a conceptual recruitment model in the aspects of theoretical foundations and empirical evidence on the factors and outcomes leading to the use of social media recruiting technology (SMART). Design/methodology/approach: A total of 4481 organizations were listed as population of the study and total 589 responses used in the study for data analysis. Selection of the sample was done on the basis of simple random sampling technique. Appropriateness of sample size was confirmed with the help of G*Power (3.1.9.2) software, which calculated sample size 326 with 99% power, multiple correlation (R) of 0.30 and at significance level of 0.05. Findings: The paper provides empirical insights into the elements of the extended unified theory of acceptance and use of technology, i.e., performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, habit, and price value have positive relations with the intention to adopt social media recruiting technology and intention impacts use of social media recruiting technology. Further, use of social media recruiting technology impacts outcome variables, i.e., social media recruiting time, cost, and recruitment quality which establish the extension of the recruitment model with all factors and outcomes. Originality: This study provides a model of employee recruitment to win the battle of acquiring human capital by using social media recruiting technology as a step towards sustainable development, which has been conceptually defined and empirically tested. The comprehensiveness of the model has never been discussed in earlier studies. Practical implications: Through this research, organizations will get an opportunity to experience enhancement in the scope of recruitment as a whole instead of considering recruitment as a traditional procedure, and the use of information technology can be expanded for progressive measures for future purposes and pandemic situations.